Experimental Studies on Mechanical Properties of Carbon Nanotube Reinforced Aluminum 7075 Composite Material - Mahendra Kumar Chidananda Swamy; Raghavendra Bommanahalli Venkatagiriyappa (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
In the present work multiwalled carbon nanotubes were added as reinforcement to aluminum 7075 matrix at 0.5%, 0.75% and 1.25% by weight proportion through stir casting technique. The mechanical properties of the produced composite were studied. The composite has considerably good tensile and wear resistance properties and hence finds its best suited application in aircraft frame and wings structures. Microstructure analysis through SEM showed a uniform distribution of the reinforcement material in the matrix. XRD graphs were taken at selected points during microscopic studies to determine the chemical composition of the matrix alloy, the reinforcement and the composite. The experimental results showed that 1.25% reinforcement in the composite material exhibited a tensile strength of 560 N/mm2 and a compression strength of 649.6 N/mm2 as the highest among the compositions. Thus, the reinforcement addition at 1.25% improved the tensile and compression strength of the composite material.